Impacting employees’ and managers’ mental health skills using a workplace-adapted mindfulness-based intervention - Bonde, Emilie Hasager; Mikkelsen, Eva Gemzøe; Fjorback, Lone Overby; Juul, Lise (Frontiers in Psychology, 2022)
Background During the past decades, the mental health of the population has been declining. Mindfulness-based stress reduction (MBSR) has been found effective in enhancing well-being along with reducing perceived stress and symptoms of anxiety and depression. Mindfulness-based interventions (MBIs) in the workplace have shown promising results relating to the mental health of employees and managers. However, the research field of organizational-level MBIs being offered to entire companies is still nascent. Practicing mindfulness may affect skills related to good mental health. Thus, the objective of this study was to investigate the impact of an organizational-level MBI on the mental health skills of employees and managers. Methods This qualitative study was part of a quasi-experimental multi-method study. Four small and medium-sized private enterprises with a total of 368 employees and managers were included. The intervention contained: 1. An obligatory introductory session on mental health and mindfulness, 2. Voluntary participation in a 10-week live online workplace-adapted MBSR course, and 3. A workshop for selected employee representatives and managers on further implementation of mindfulness in the organization. A total of 27 focus group interviews including 76 respondents were conducted pre- and post-intervention. Verbatim transcription was performed. Data was analyzed using inductive qualitative content analysis. Results Through analysis, four pre-intervention categories emerged: 1. Bodily sensations and awareness in stressful situations, 2. Reactive and passive behavior during stressful situations, 3. Differences in perception as a stressor, 4. Self-criticism and low ability to practice self-care. Six post-intervention categories were identified: 1. Enhanced ability to be aware in the present moment, 2. Increased acknowledgement of how others may view things differently from oneself, 3. Increased kindness to oneself and being able to practice self-care, 4. Moving from reactive to responsive behavior in stressful situations, 5. Mindfulness as an accelerator for an ongoing personal process and 6. Practicing mindfulness – setting time aside or being mindful in everyday life. Conclusion This study indicates that it is possible to enhance employees’ and managers’ mental health skills using an organizational-level MBI. Enhanced awareness in the present moment transcended through post-intervention categories, facilitating increased self-kindness and responsive behavior in stressful situations.